The Relationship Between DNA Mismatch Repair Status and Clinicopathologic Characteristics in Colon Cancer - Mehmet Doğan,; Mehmet Kılıç,; Hayriye Tatlı Doğan, (Turkish Journal of Gastroenterology, 2024)
Background/Aims: DNA mismatch repair (MMR) proteins are essential for repairing genetic mutations that occur during DNA replication. Deficiency of MMR proteins results in a phenotype called microsatellite instability (MSI), which occurs in Lynch syndrome as well as sporadic colorectal cancers (CRC), and it is associated with several clinicopathological features. We aimed to investigate the association of the loss of MMR proteins with clinicopathologic considerations in our CRC series.Materials and Methods: In this retrospective study, DNA MMR protein status in CRC is evaluated in a total of 200 colorectal resection specimens by immunohistochemistry (IHC) for MLH1, MSH2, MSH6 and PMS2 protein expression. The BRAF mutation was investigated by the real-time PCR in cases with loss of MLH1 protein expression. The relationship between MMR status and clinicopathological parameters was investigated statistically.Results: Loss of MMR protein expression was detected in 26 of 200 CRC cases. The BRAFV600E mutation was detected in 2 of the cases with MLH1 loss and accepted as sporadic. The remaining 24 cases (12%) were identified as Lynch syndrome candidates. There were statistical differences observed regarding the presence of tumor-infiltrating lymphocytes (P < .001), Crohn’s-like reaction (P = .001), expansile growth (P < .001), tumor heterogeneity (P < .001), mucinous differentiation (P < .001), and presence of metastatic lymph nodes (P = .045) between sporadic cases with preserved MMR and Lynch candidates. However, difference in the survival rates between sporadic cases and Lynch candidates was not significant.Conclusion: Immunohistochemical staining for MMR is a practical method for predicting MSI phenotype as well as Lynch candidates. MMR expression status was found to be associated with certain clinicopathological features some of which also have prognostic significance. Cite this article as: Doğan M, Kılıç M, Tatlı Doğan H. The relationship between DNA mismatch repair status and clinicopathologic characteristics in colon cancer. Turk J Gastroenterol. 2024;35(9):718-725.